Judd Ofelt Analysis and Optical Properties of Eu\(^3 + \) Doped Tellurite Glasses - Hong, Tran Thi; Dung, Phan Tien; Quang, Vu Xuan (Communications in Physics, 2014)
In this work, the structural characteristic and photoluminescence properties of Eu\(^3 + \) doped B\(_2\)O\(_3\)-TeO\(_2\) -ZnO-Na\(_2\)O glasses were investigated. These glasses were prepared by a melting method in air, combined with thermal annealing at 350\(^°\)C, 450\(^°\)C and 550\(^°\)C for different duration times. The structural analysis results of these glasses revealed the formation of micro-crystals in the annealed host glass. The photoluminescence spectra of Eu\(^3 + \) doped in these samples were observed. The local vibration mode around Eu\(^3 + \) ions was investigated by the phonon side-band (PSB) associated with \(^7\!F_0-^5D_2\) transition of Eu\(^3+\). Judd-Ofelt parameters were then evaluated based on photoluminescence spectra and the luminescence intensity ratios of \(^5D_0 → ^7\!F_J\) (\(J=2, 4\) and 6) to \(^5D_0 → ^7\!F_1\) transition were predicted. The obtained results were then used to calculate \(Ω _2, Ω _4, Ω _6 \) parameters based on Judd-Ofelt theory. These \(Ω _2\), \(Ω _4\), \(Ω _6\) parameters allow to derive radiative properties of Eu\(^3 + \) ions in glass material such as transition probabilities, radiative lifetimes and peak stimulated emission cross-section for the \(^5D_0 → ^7\!F_J\) transitions